Efeito do pré-condicionamento isquêmico no desempenho da natação em uma série intervalada de alta intensidade - Ferreira, Thiago Henrique Nunes [UNIFESP] (2016)
Ischemic preconditioning (IPC) has been shown to improve aerobic and anaerobic performance. However, its effect on high-intensity interval exercise has been controversial, placebo effect has not been adequately controlled, and nocebo effect has not been taken into account. Thus, we investigated the effect of IPC on swimming performance in well-trained athletes submitted to a high-intensity interval training (HIT) set controlling placebo and nocebo effects. Short-distance swimmers were randomized to two groups. One group [n = 15, 24 ± 1 years (mean ± SEM)] was exposed to IPC (ischemia cycles lasted 5 min) and control (CT, no ischemia). Another (n = 15, 24 ± 1 years) was exposed to a placebo intervention (SHAM, ischemia cycles lasted 1 min) and CT. All subjects were informed that IPC and SHAM would improve performance compared to CT and would be harmless despite ischemia sensations. The SIT set consisted of six 50-m all-out efforts repeated every 3 min. Improvement expectation after IPC and SHAM exposure was 87% and 73% (P = 0.66), respectively. IPC reduced worst sprint time (IPC: 35.21 ± 0.73 vs. CT 36.53 ± 0.72 s, P = 0.04) and total sprints time (IPC: 203.7 ± 4.60 vs. CT 206.03 ± 4.57 s, P = 0.02), besides augmented swimming velocity (IPC: 1.45 ± 0.03 vs. CT 1.44 ± 0.03 m/s, P = 0.049). Blood lactate concentration (P = 0.20) and perceived effort (P = 0.22) did not change with IPC. SHAM did not change sprints time, swimming velocity, blood lactate concentration, and perceived effort (P > 0.05). In conclusion, IPC enhanced swimming performance of well-trained athletes in a SIT set, whereas a placebo intervention did not change swimming performance. Thus, the results support that the IPC has ergogenic effect, independently of the PL effect.